The gravitational models on the base of tensor field in minkowski space-time - Kirichenko, V.T.; Kudussov, A.S.; Musenova, E.K. (Publishing House of the KarSU named after E.A.Buketov, 2009)
The class of classical gravitational tensor field in the Minkowski space-time models based on universal procedure of theories «free lagrangian” gravitational “dressing” has been developed. The procedure consists in operation of a "gravitational" operator on a "free lagrangian”. The "gravitational" operator is specific for each model of the class. The common structure of those operators has been shown. The possible models are discussed. The construction of A. Einstein’s theory of general relativity (GRT) is represented as an example of the used method. Mathematical realization of “co-variantization” principle for GRT has been given.
Keywords: gravitational tensor field; Minkowski space-time models; gravitational operator